Implementasi Kebijakan Pelabelan Keluarga Penerima Manfaat (KPM) Program Keluarga Harapan (PKH) Ditinjau dari Perspektif Fiqh Siyasah Tanfiziyah (Studi Kasus Nagari Bahagia Padang Gelugur Pasaman Timur) - Ade Yulia Rahmi; Raymond Dantes (Lembaga Yasin AlSys, 2026)
Poverty remains a social problem that requires targeted, transparent, and equitable mitigation policies. This study aims to analyze the implementation of the house-labeling policy for Beneficiary Families of the Family Hope Program (KPM PKH) in Nagari Bahagia, Padang Gelugur, East Pasaman, and to examine it from the perspective of fiqh siyasah tanfiziyah. This study used field research with a qualitative approach. Data were collected through observation, interviews, and documentation with the nagari government, PKH facilitators, community leaders, and beneficiary families. The results showed that the KPM PKH labeling policy was implemented to improve the targeting accuracy of social assistance, strengthen the transparency of beneficiary data, and encourage independent graduation among communities that had become economically capable. However, this policy also caused social impacts in the form of shame, negative stigma, and discomfort among some assistance recipients. From the perspective of fiqh siyasah tanfiziyah, the KPM PKH labeling policy can be justified because it aims to realize public welfare (maslahah ‘ammah) and ensure that social assistance is received by communities that truly need it. The conclusion of this study affirms that the social assistance labeling policy needs to be implemented by considering the principles of public welfare, justice, protection of the dignity of assistance recipients, and prevention of social and psychological harm.